Integrasi Kurikulum Pada Sekolah Adiwiyata - Mahdi, Ahmad; Erihadiana, Mohamad; Ruswandi, Uus (Eduprof : Islamic Education Journal, 2023)
Curriculum according to wikipedia Indonesian is a set of subjects and educational programs provided by an educational institution that contains lesson designs that will be given to lesson participants in one period of education. Etymologically, curriculum comes from English, namely the word curriculum which means lesson plan (Echolz:1984). The word Curriculum itself comes from the word "Currere which means to run fast, rush, explore, live, and strive (Hassibuan:1979). In Webster's 1857 dictionary, curriculum is clearly defined as the design of a number of subjects that students must master in order to move up or get a diploma (complete their studies). According to Soedijarto, the curriculum is a series of learning experiences and activities that are planned to be overcome by students in order to achieve the learning goals that have been set by an authorized educational institution. As for Indonesia, in Law No.20 of 2003 article 1 paragraph (19), the constitution states that the curriculum is a set of plans and arrangements regarding the objectives, content and learning materials as well as the methods used as guidelines for the implementation of learning activities to achieve certain educational goals. The issue of global warming which results in climate change so as to aggravate the decline in the quality of the environment therefore it is necessary to carry out environmental protection and management starting from the world of education. It was Mr. H. Suwondo, B.A who pioneered and initiated that SMA 1 Pandeglang at that time had just occupied a new land, the conditions were not comfortable and reflective for teaching and learning activities. Continued by Drs. H. Epi Saefudin, M. Pd, the Principal at that time and an educator who was also an observer and environmentalist. With various steps, lobbying, communication and starting from the 2008/2009 school year, SMA Negeri 1 Pandeglang was appointed as one of the adiwiyata schools. Education unit curriculum (KTSP) by integrating the curriculum of environmental-based education units or adiwiyata. Marked by the content of the lesson curriculum combines school-based and Adiwiyata.Adiwiyata as a school program aims to create good conditions for the school to become a place of learning and a place of awareness of school residents, both educators, education staff, students and the community around the school, in an effort to encourage environmental rescue and sustainable development which can finally realize a school that cares and has an environmental culture